Money Laundering Through Art A Criminal Justice Perspective - De Sanctis, Fausto Martin. (Springer International Publishing : Imprint: Springer, 2013)
This volume provides a bird’s eye view of novel ways in which money is laundered through illegal activities involving art. Criminals and those involved in illegal activities have discovered the art world to be an effective and clandestine arena through which they can launder money internationally. Unfortunately, investigators, prosecutors, judges and regulatory agencies in most countries are not equipped to accurately detect, investigate and prosecute this type of criminal activity. Furthermore, international laws and treaties involving the art world have many loopholes that can potentially lead to the laundering of large sums of money.   Addressing this gap in the literature, Money Laundering Through Art: A Criminal Justice Perspective can serve as a guide for academics, prosecutors, judges, law enforcement officials and others involved in efforts to curb money laundering and the financing of terrorism. It provides an overview of methods of money laundering through art, as well as specific case studies. Additionally, this book reveals why new techniques used by criminals have been largely neglected by law enforcement in many countries.   The author, drawing from his own experience with the matter in both Brazil and the United States, makes a case for broader institutional and regulatory improvement, extending beyond mere regulation of the art market. He concludes with a number of concrete recommendations to improve the fight against illegal money laundering via artwork.